In situ synthesis of ligand reduced/capped silver nanoparticles and the effect of temperature and ligand structure on the size of silver nanoparticles - Kasture, M. B.; Patel, P.; Prabhune, Asmita; Ramana, C. V.; Kulkarni, A. A.; Bhagavatula L. V. Prasad (Journal of Chemical Sciences, 2008)
We report in situ synthesis of silver nanoparticles using biosurfactants called sophorolipids as reducing and capping agents. We further study the effect of temperature and the structure of sophorolipid on the size of silver nanoparticles obtained. The silver nanoparticles were characterized by UV-visible, transmission electron microscope (TEM) and light scattering (DLS) analysis techniques.
Keywords: dynamic light scattering; Nucleation and growth; silver nanoparticles; Sophorolipid